Studi Bahaya Seismik dengan Metode PSHA (Probabilistic Seismic Hazard Analysis) di Nusa Tenggara Barat Menggunakan Data Gempa Tahun 1900 - 2023 - Ananda, Nadya Rezky; Pujiastuti, Dwi (Jurnal Fisika Unand, 2024)
Research has been conducted on earthquake hazard in West Nusa Tenggara using the Probabilistic Seismic Hazard Analysis (PSHA) method. Earthquake data from 1900 2023 were obtained from the United States Geological Survey (USGS) catalog. PSHA uses earthquake parameters that produce maximum ground acceleration (PGA). The PGA value is calculated using an attenuation function based on the earthquake source. The results of the analysis show that for West Nusa Tenggara, the maximum PGA is 0,65 g with a 10% return event probability in 50 years and 0,71 g with a 2% return event probability in 50 years. Areas with high earthquake risk with 2% and 10% return event probability in 50 years are Sumbawa with PGA ranges of 0,26-0,68 g and 0,18 0,26 g and Lombok with PGA ranges of 0,26-0,47 g and 0,26-0,42 g, respectively. Areas with the lowest to moderate earthquake risk with a probability of re-occurrence of 2% and 10% in 50 years are Bima with a PGA of 0,37 g and 0,26 g, Badjo with a PGA range of 0,37-0,47 g and 0,26 g, and Kore with a PGA range of 0,26-0,37 g and 0,18-0,26 g, respectively. Based on the PGA values obtained, Sumbawa is an area that has the greatest level of earthquake risk due to its location close to the subduction zone.